ПРОБЛЕМИ МОЛОДІ У ФАХОВІЙ САМОРЕАЛІЗАЦІЇ ЯК СИСТЕМНА ПРОБЛЕМА: АНАЛІЗ СОЦІАЛЬНИХ ЧИННИКІВ - Siry, Evgeny; Sira, Oksana (Zhytomyr Ivan Franko State University, 2024)
The material of the article is devoted to the possibilities of professional self-realization of young people in the problem of employment, and the analysis of its social factors. It was shown that the generation of the problems of ensuring employment of young people is determined not only by the low level of their competitiveness in the labor market, the lack of necessary practical experience, work experience in the profession, but also by the access of young people to relevant public resources (economic, legal, social), the level of their economic, social and cultural capital. This is also the inadequate assessment of the objective conditions and opportunities of employment in accordance with their own profession and preferences. The article considers a number of social factors of generating the problem of professional certainty and its implementation, in particular: family factors, subjective (overestimated self-esteem, professional inflexibility), educational, stratification, and other situational factors. The educational factor of the problem is considered separately, where there is a mismatch of the content of professional education with modern market challenges, its inconsistency with the requirements and needs of the present. The problematic factor of the employer's pragmatism and its non-constructive role in the possibility of professional realization of a young employee is separately assessed (extreme pragmatism, inflexibility in personnel matters, additional unprofessional burden on a young employee). A number of socio-professional factors of youth competitiveness in the employment market have been determined, which are generative both by external social conditions and micro social components. Involving non-formal education with its revealed potential was positioned as one of the means of partially solving this problem. It is shown that non-formal education is indeed an important factor for self-realization and integration of students in education. And in view of modern realities - the challenges of war, the demand for non-formal education as an additional resource for formal education is growing even more.